Drug release from polyelectrolyte coated PLGA microparticles - Yap, Shirley Zhi Yin. (2011)
This report documents the investigation of drug release from polyelectrolyte coated PLGA microparticles. Currently, PLGA microparticles are widely used in most drug delivery systems for controlled drug release, but the problem of burst release still remains. Polyelectrolyte coating is thus employed to overcome this problem due to its unique properties for inhibiting release. In this project, polyelectrolyte multilayer (PEM) has been successfully coated onto PLGA particles loaded with various kinds of drugs ranging from hydrophobic drug (fluorescein diacetate, FDA) to hydrophilic drug (fluroscein isothiocyanate labeled dextran, FITC-D) using the emulsion-evaporation technique. A positive drug release retardation result of at least 80% is achieved for medium-sized FITC-D 70 kDa and 250 kDa particles. For FITC-D 70 kDa medium particles, the retardation can be sustained higher than that of the FITC-D 250 kDa particles. On the other hand, PEM shows no effect for both FDA and fluorescein. Also, the effect of washing agents during the coating process was not shown significantly throughout the drug release course. Lastly, a comparison between the medium and large particles was conducted. However, the results obtained show that particle size does not affect drug retardation significantly as of now. Up till the time of report submission, only preliminary data were collected. Further evaluation works are still ongoing to collect more accurate and reliable results.